Barriers for resuming endoscopy service in the context of COVID-19 pandemic: a multicenter survey from Egypt - Elshaarawy, Omar; Lashen, Sameh Aldesoky; Makhlouf, Nahed A.; Abdeltawab, Doaa; Zaghloul, Mariam Salah; Ahmed, Rasha M.; Fathy, Hayam; Afifi, Shimaa; Abdel-Gawad, Muhammad; Abdelsameea, Eman; Abd-Elsalam, Sherief; Mohamed, Salem Youssef; et al. (World journal of gastroenterology, 2020)
Barriers for resuming endoscopy service in the context of COVID-19 pandemic: A multicenter survey from Egypt